2002
DOI: 10.1063/1.1480830
|View full text |Cite
|
Sign up to set email alerts
|

A framework for predicting accuracy limitations in large-eddy simulation

Abstract: The accuracy of large-eddy simulations is limited, among other things, by the quality of the subgrid parametrization and the numerical contamination of the smaller retained flow structures. We characterize the total simulation error in terms of the “subgrid-activity” s, which measures the relative turbulent dissipation rate (0⩽s⩽1) and the “subgrid resolution” r. This analysis is applied to turbulent mixing of a “Smagorinsky fluid” using a finite volume discretization of fourth order accuracy. On fixed coarse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
199
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(206 citation statements)
references
References 5 publications
6
199
0
1
Order By: Relevance
“…Although comparison with filtered DNS data is impossible here, we observe that the smoothed Leray dynamics is essentially captured as r ϭ⌬/hу4. 12 The tail of the spectrum increases with Re, indicating a greater importance of small scale flow features. Improved subgrid resolution shows a reduction of these smallest scales, consistent with the reduced numerical error.…”
Section: ͑4͒mentioning
confidence: 99%
See 1 more Smart Citation
“…Although comparison with filtered DNS data is impossible here, we observe that the smoothed Leray dynamics is essentially captured as r ϭ⌬/hу4. 12 The tail of the spectrum increases with Re, indicating a greater importance of small scale flow features. Improved subgrid resolution shows a reduction of these smallest scales, consistent with the reduced numerical error.…”
Section: ͑4͒mentioning
confidence: 99%
“…At fixed ⌬, variation of the subgrid resolution r allows an independent control over flow smoothing and numerical representation. 12 Simulation results obtained in this way are properly smoothed for k⌬ Ͻ2 . At constant ⌬ the inclusion of modes with higher wavenumber k in case rϾ1 allows to approach the gridindependent solution to the ''fixed-⌬'' problem.…”
Section: ͑4͒mentioning
confidence: 99%
“…The volumeaveraged sgs is 18%, 19% and 21% of the total volume-averaged dissipation, for the three Reynolds numbers considered. Using LES and DNS of mixing layers, Geurts & Fröhlich (2002) found that, when this measure of 'subgrid-activity' is less than 30%, the modelling errors are less than 1%. Figure 12 shows the terms in the budget of the turbulent kinetic energy K = u i u i /2.…”
Section: Open Duct: Reynolds Stressesmentioning
confidence: 99%
“…A consequence of this characteristic of self-consistent hybrid methods is that, in the budget of the resolved kinetic energy, the molecular dissipation rate ε R = νS i jS i j , wherẽ S i j denotes the filtered strain tensor, an overbar the ensemble average and ν the molecular viscosity, remains negligible compared to the so-called turbulent dissipation −τ i j sfsS i j [13], where τ i j sfs denotes the subfilter (SFS) stress tensor.…”
Section: Energy Ratio Rmentioning
confidence: 99%